INFLUENCE OF SALIVA AND BLOOD CONTAMINATIONTOWARDSCLASS II COMPOSITERESTORATION TENSILE BOND STRENGTH USING UNIVERSAL BONDING AGENT: AN IN-VITRO STUDY - Effendy Rusli,Wandania Farahanny, Dennis Dennis (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Background:Class II composite restorationhave apoor resin-dentin bonding on cervical part/surface. Fluid contamination is frequently occur at cervical caries due to rubber dam isolation is not feasible. Saliva and blood contamination occurs the most often,causing the bonding between resin and rest tooth structure is compromised. Aim: This study aims to evaluate the influence/effect of Saliva and Blood Contamination towardsClass II Composite Restoration Tensile Bond Strength Using Universal Bonding Agent. Method: Thirty human maxillary premolars were selected and divided into three groups. In group 1, 2, and 3, class II MOcavities were prepared, contaminated, water rinsing, bonding application then restored. Group 1 were contaminated with saliva, Group 2 were contaminated with saliva and blood. No Contamination were applied to Group 3 as control group. All the teeth were stored in saline solution for 24 hours beforethermocycled. Tensile bond strength was measured by using Universal Testing Machine. Data were analyzed statistically by One Way ANOVA and Post Hoc LSD Test. Result: The result showed that the group 2 had the lowest tensile bond strength and group 3 had the highest tensilebond strength. The difference between groups was statistically significant (p<0,05). Conclusion: It can be concluded that contamination before the application of bonding agent reduces tensile bond strength.